Asignación Universal por Hijo para la Protección Social: aproximación al enfoque de derechos y su concepción de los inmigrantes en Argentina - Guzzo, Giuliana; Navarro Sanz, Gonzalo Gabriel (Comparative Cultural Studies: European and Latin American Perspectives, 2018)
This article has the purpose to analyze and reflect the relationship between AUHPS and the migration phenomenon in Argentina. Concretely, it refers that although there was a social and political progress in the country, of respect and recognition to rights of the sons of parents of workers in infomality. This was not the same with Immigrant workers in informal and their families. In this sense, this article tries to find and show meanings and representations of immigrant workers in Argentina, especially Bolivian women who work in Guaymallén, Mendoza State and because of their labor situation they are directly and indirectly connected with the social and political issues.